Prinsip Penerapan Sistem Penghawaan dan Pencahayaan Alami pada Bangunan Rumah Susun Sewa Mabes TNI di Bekasi - Farrah Amabella Yuwanda; Lia Rosmala Schiffer (Jurnal Arsitektur Wastu Padma, 2023)
The article comes from research which aims to determine the principles of applying natural ventilation and lighting to rental flats at the TNI Headquarters in Bekasi. The design of natural ventilation and lighting systems in flats is part of efforts to meet health and fitness goals for residents economically and effectively. The research method used is a survey technique by conducting observations and literature studies to obtain information regarding applications in building design. From the results of the discussion it can be stated that the principles that must be considered are building orientation, floor plan, area of ​​light openings and effective ventilation.